The Reform Process Of The Albanian Educational System: Its Problems And Challenges - et. al., PhD. Merita Isaraj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Albanians belong to the population who are particularly differentiated by their education. For many years Albanians were categorically denied the right of education in their mother tongue by the former Turkish Empire. Accordingly, the first school in Albanian goes back to the last decade of XIX-th century. In this aspect we can mention that until 1945 the existence of high schools was very low in number, while as far higher education is concerned, it was not existent at all. After 1945, the communist governing authorities undertook fundamental investment in education by opening primary and high schools nationwide, as well as the first University in 1957. However, despite the important results it achieved, it was absolutely politicized. After the fall of communism, the educational system faced new challenges. The imperative problem was a deep reform to meet the requirements of the new historical reality. Consequently, after 1991 the education system in Albanian was involved in deep reforms such as keeping away from politics, reconsideration of textbooks, teaching plans or programs, management mode of school, respecting the children rights etc. All these radical and large scale reforms were not only helpful, but considerably influenced the rise of teaching and learning quality. Anyhow, in some cases the reform application did not always produce the expected results. They influenced the progress of the teaching process. Therefore, it is crucial that the educational system in Albania should seriously consider the long-term influence of these problems by the compilation of accurate and strategies about pre- university education.